2016
DOI: 10.1088/1674-1056/25/2/023402
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission from 424-MeV/u C ions impacting on selected target

Abstract: The K-shell x-rays of Ti, V, Fe, Co, Ni, Cu, and Zn induced by 424-MeV/u C6+ ion impact are measured. It is found that the K x-ray shifts to the high energy side and the intensity ratio of Kβ/Kα is larger than the atomic data, owing to the L-shell multiple-ionization. The x-ray production cross sections are deduced from the experimental counts and compared with the binary encounter approximation (BEA), plane wave approximation (PWBA) and energy-loss Coulomb-repulsion perturbed-stationary-state relativistic (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Therefore, it is proposed that the observed x rays are produced by the swift C 6+ ions with the same energy, even though they result from the different atomic layers. Taking into account of the self-absorption of the target and the absorption of air between the target and the detector, the experimental x-ray production cross section can be extracted from the thin target formula and can be expressed as 27 , 48 : where μ is the absorption coefficient of the x ray. N X is the obtained counts of the x ray which were extracted by fitting the x-ray spectrum with Gauss function of origin software, namely, the area under peak of the fitted spectral line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is proposed that the observed x rays are produced by the swift C 6+ ions with the same energy, even though they result from the different atomic layers. Taking into account of the self-absorption of the target and the absorption of air between the target and the detector, the experimental x-ray production cross section can be extracted from the thin target formula and can be expressed as 27 , 48 : where μ is the absorption coefficient of the x ray. N X is the obtained counts of the x ray which were extracted by fitting the x-ray spectrum with Gauss function of origin software, namely, the area under peak of the fitted spectral line.…”
Section: Resultsmentioning
confidence: 99%
“…In the low and intermediate energy region, a great deal of experimental works have been carried out focusing on such process by x-ray measurement [13][14][15][16][17][18] , and many well-known theories have been developed to describe such inner-shell ionization, such as, binary encounter approximation (BEA) 19 , plane wave Born approximation (PWBA) 20 , modified PWBA model by energy-loss, Coulomb-repulsion, perturbed-stationary-state and relativistic (ECPSSR) and refined ECPSSR at low energies with modification of united and separated atom approximation (ECUSAR) [21][22][23] . However, only a limited number of studies have been undertaken in the very high energy region, especially for the fast ions with energy greater than one hundred MeV per mass unit (MeV/u) [24][25][26][27][28] . It is unclear which existing theory molded is more suitable in such a high energy region.…”
mentioning
confidence: 99%
“…A Chinese cohort of 84 AS patients showed that the gut microbiota was perturbed in untreated AS patients with diagnostic potential, and some AS-enriched species might be triggers of autoimmunity by molecular mimicry. More importantly, different inflammatory arthritis share some common microbial signatures (Zhou et al, 2020) such as A. fermentans, B. coprophilus, P. distasonis, E. siraeum, and P. copri as markers specifically enriched in the AS gut, and increased pathways including oxidative phosphorylation, LPS biosynthesis, and glycosaminoglycan degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years, more than 100 published papers have focused on the interaction between the microbiome and AS (Costello et al, 2013;Xu et al, 2016;Simone et al, 2018;Watad et al, 2018;Huang et al, 2020;Zhou et al, 2020). Bacteroides coprophilus, Parabacteroides distasonis, Eubacterium siraeum, Acidaminococcus fermentans, and Prevotella copri were enriched in AS patients, and pathway analysis revealed increased oxidative phosphorylation, LPS biosynthesis, and glycosaminoglycan degradation (Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation